A research on the evaluation of nutrition knowledge levels of soccer coaches - Aka, Hasan (Progress in Nutrition, 2020)
Study Objectives: The study aimed to compare the nutritional knowledge levels of soccer coaches according to their educational status, different league levels, and job variables. Methods: A total of 240 coaches, including technical directors (n = 73), assistant coaches (n = 74), goalkeeper coaches (n = 43), performance specialists / analysts (n = 50) participated in the study voluntarily. Nutritional knowledge of soccer coaches was determined by “The Nutrition for Sport Knowledge Questionnaire’ (NSKQ). One-Way ANOVA test was used to determine the difference between the groups, and the Scheffe test, one of the Post-hoc tests, to determine which group the difference was originated from. Results: As a result of the statistical analysis, while there was no significant difference between the nutrition knowledge total scores of soccer coaches and both the league level and job description, performance specialists/analysts had higher scores in the job description variable. It was determined that sports science and university graduate coaches had higher total score values with their weight control, sports nutrition, and alcohol sub-dimensions compared to high school and undergraduate coaches (p